2002
DOI: 10.1094/cchem.2002.79.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flour Particle Size and Starch Damage on Processing and Quality of White Salted Noodles

Abstract: Cereal Chem. 79(1):64-71Several reduction grinding conditions were used on a Canadian Western Red Spring (CWRS) farina to yield flours of comparable protein content within three specific particle size ranges (132-193, 110-132, 85-110 µm) at three starch damage levels (3.0, 3.9, 7.0 Megazyme units). White salted noodles (1% w/w NaCl) were initially processed at a fixed absorption (32%). Dynamic oscillatory and large deformation creep measurements indicated that doughs with lower starch damage, thick or thin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 7 publications
6
96
1
1
Order By: Relevance
“…Flour ash content has been rated as one of the important specifications because it affects noodle colour negatively as reported by Hou and Kruk (1998). In a study by Hatcher et al (2002) it was reported that after being stored for two to five days, fresh noodles had a tendency to darken, which holds true for our observations too. Darkening usually happens due to the protein content of noodles.…”
Section: Yield Ratio (Noodles)supporting
confidence: 85%
“…Flour ash content has been rated as one of the important specifications because it affects noodle colour negatively as reported by Hou and Kruk (1998). In a study by Hatcher et al (2002) it was reported that after being stored for two to five days, fresh noodles had a tendency to darken, which holds true for our observations too. Darkening usually happens due to the protein content of noodles.…”
Section: Yield Ratio (Noodles)supporting
confidence: 85%
“…Very fine particle size flour may be indicative of high starch damage, which should be avoided, due to its competition for water with gluten during mixing. Increased starch damage is also associated with poor noodle colour and undesirable high cooking loss and excessive surface swelling (Hatcher, Anderson, Desjardins, Edwards, & Dexter, 2002).…”
Section: Flourmentioning
confidence: 99%
“…Both the impact force (the main force) and the shear force (the minor force) in a hammer mill produce a smaller average particle size than the compressive force of a roller mill (BarbosaCánovas et al, 2005). Generally, a fine particle size has the highest swelling power and form a rigid gel structure which results in additional strength in comparison with a coarse particle size (Chen et al, 2003b;Hatcher et al, 2002). Flour from wet grinding had significantly the lowest damaged starch content of 2.78% on a dry basis (%db), as the water in the wet grinding process absorbed the heat during grinding, and the plentiful moisture content of the rice kernels resulted in a soft structure.…”
Section: Grinding Processmentioning
confidence: 99%